Seismic vulnerability assessment method for vernacular architecture - Ortega, Javier (2018)
The valorization and preservation of vernacular architecture, as well as traditional construction techniques and materials, is a key-element for cultural identity. As part of this essential objective, the present paper focuses on vernacular architecture earthquake preparedness. Earthquakes come unexpectedly, endangering in-use vernacular architecture and the population who inhabits it. However, conservation efforts are often mainly focused on historical construction and monuments. Furthermore, more detailed and sophisticated approaches typically used for monumental buildings require time, cost and resources that are not commonly assigned to the study of vernacular constructions. That is why the development of a simplified method for the seismic vulnerability assessment of vernacular architecture is of paramount importance. The paper firstly provides a brief overview of seismic vulnerability assessment methods, specifically the vulnerability index method, on which the proposed method is based. Then, the paper presents the procedure that was followed for the development of the seismic vulnerability assessment method for vernacular architecture proposed, which includes: (a) the identification and selection of constructive aspects and parameters that most influence the seismic behavior of the building; (b) the definition of the parameters seismic vulnerability classes by means of numerical parametric analysis using detailed finite element (FE) modeling and nonlinear static (pushover) analyses; and (c) the definition of the parameters weight, according to a statistical analysis performed on the results of the parametric study. Finally, the paper shows, as an example, the numerical strategy followed for the definition of the classes of one parameter.